GENERAL APPROACHES TO THE SAFETY OF MILITARY GEOGRAPHIC INFORMATION SYSTEMS - Oleksandr A. Chornoknyzhnyi (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
In the course of design and creation of military geographical information system it is necessary to define the main directions of the task solution of safety approaches of such system functioning. In the article the main safety approaches of geographic information system functioning and the indicators system are applied for its assessment were analyzed.